DIGITAL MARKETING ASSISTANCE TO ENCOURAGE CREATIVE ECONOMY IN CIHAMERANG VILLAGE - Firdaus, Asep; Siwiyanti, Leonita (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2024)
The purpose of this service is to provide digital marketing assistance in Cihamerang Village, West Java, to encourage the creative economy and utilize the potential that exists there. The village has unique products and beautiful natural landscapes, but product marketing problems have hindered the growth of its creative economic potential. The solution to using digital technology in marketing local products is digital marketing assistance. Basic digital marketing courses, website creation, engaging content, search engine optimization, and online store management are all part of this program. As a result, local businesses began to use digital marketing strategies and expand their market. The delivery of easy-to-understand material and the presence of tech-savvy KKN students are two factors that support this program. However, there are obstacles such as hectic schedules and technical issues associated with website creation. The purpose of empowerment through digital marketing assistance is to encourage the creative industry of Cihamerang Village, increase community prosperity, and encourage sustainable economic growth. Positive results have been shown, and the program is expected to continue to improve the village's creative economy and maximize the region's potential for a better.